Gene expression in peripheral blood cells for differentiation of active and latent tuberculosis infection in children and adolescents - A. A. Elov; M. A. Vladimirskiy; S. V. Smerdin; O. I. Elufimova (Туберкулез и болезни лёгких)
The objective: to analyze the expression of certain genes in the blood cells of children and adolescence to differentiate the active and latent phases of tuberculosis infection.Subjects and methods. Peripheral blood samples collected in 36 pediatric patients with latent tuberculosis infection and 24 patients aged 1 to 16 years undergoing in-patient treatment for pulmonary tuberculosis were tested. A modified method for isolating messenger RNA and reverse transcriptional polymerase chain reaction was used to identify the transcription of six genes selected for analysis.Results. In a comparative study of the expression values of six promising genes in blood cells in the study of two groups of children and adolescents with latent and active tuberculosis infection, it was found that the most differentiating feature for determining active tuberculosis infection was a significantly higher level of expression of PDCD1 gene encoding PD1 lymphocyte receptor. At the same time, the sensitivity to detect the active infection was found to be 95.8%, specificity – 94.4%, the accuracy of the positive prognosis of active tuberculosis infection was 93.3%.